Risk Assessment of Groundwater Abstraction Vulnerability Using Spatial Analysis: Case Study at Salatiga Groundwater Basin, Indonesia - Thomas Triadi Putranto; Tri Winarno; Axel Prima Agita Susanta (Geological Agency, 2020)
DOI:10.17014/ijog.7.2.215-224Salatiga Groundwater Basin (SGB) is located in Java Island, Indonesia. Administratively, it covers Semarang Regency, Salatiga City, and Boyolali Regency. Industry and community use groundwater to fulfil their daily need. Increasing number of deep wells that extract groundwater will cause some environmental problems, such as lowering groundwater level and subsidence at SGB. Thus, there is a need to assess the adverse impacts of groundwater abstraction. Risk assessment of groundwater vulnerability due to abstraction is the goal of this study. The research method was taking account of weighting of geological parameters, such as response characteristics of the aquifers, characteristics of aquifer storage, aquifer thickness, piezometric depth, and distance from the shoreline to conduct the groundwater vulnerability mapping. It was then overlaid on a map of regional spatial plan to develop the map of vulnerability risk due to abstraction. The groundwater vulnerability due to abstraction is categorized in the medium level. After being overlaid by the land use map, the risk of groundwater vulnerability due to abstraction is classified into three kinds, which are low, medium, and high. Regions with a low class can be neglected. Areas with moderate risk require an exhaustive review of technical requirements of the use of borewell. Areas with high-risk need a comprehensive consideration to use artesian wells by monitoring wells with drill licenses, tightening the permit to add new production wells, and conducting periodic review of groundwater monitoring.